New Trends In Elt: Blending Disciplines For 21st Century Foreign Language Learning - Tütüniş, Birsen (My University, 2019)
The quality of foreign language teaching improves so long as foreign language teacher education is under constant change according to the challenging demands of age we live. The vision for 21st century learning P21 (Bellanca, 2010) offers a holistic and systemic view of how we can reconceptualize and reinvigorate public education bringing together all the elements- 21st century student outcomes and 21st century education support systems- into a unified framework. The main purpose is stated to be the preparation of the students for a better learning that would support them in their lifelong struggles. The belief that doing well in school no longer gurantees a lifelong job or career, as it did in the past. Future learning is highly different from the past. It has been proved by the research (Higgins, May, 2011) that improving teacher effectiveness has a great impact on learner outcomes.Therefore, teacher knowledge needs to be enhanced by blending all disciplines into one . This paper will focus on the new trends in English Language teaching and their effectiveness on learner outcomes.
Keywords: İngilizce Yabancı Dil; Eğitim ve Öğretim; Başarı; English Foreign Language; Education and Training; Success